2012
DOI: 10.1073/pnas.1202408109
|View full text |Cite
|
Sign up to set email alerts
|

Distinct CD4 + helper T cells involved in primary and secondary responses to infection

Abstract: Helper T cells are critical for protective immunity, CD8 + T-cell memory, and CD4 + recall responses, but whether the same or distinct CD4 + T cells are involved in these responses has not been established. Here we describe two CD4 + T cells, LLO118 and LLO56, specific for an immunodominant Listeria monocytogenes epitope, with dramatically different responses to primary and secondary infection. Comparing in vivo responses, LLO118 T cells proliferate more strongly to primary infection, whereas surprisingly, LLO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
114
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(124 citation statements)
references
References 30 publications
6
114
3
Order By: Relevance
“…By comparing memory T cells generated after priming with either high dose/low affinity or low dose/high affinity antigen, our data additionally show that T cells with a similar history of primary expansion have a similar capacity to expand during secondary infection, independent of effector lineage. These data are consistent with a recent report showing an inverse correlation between primary T-cell expansion and memory T-cell development (40).…”
Section: Discussionsupporting
confidence: 83%
“…By comparing memory T cells generated after priming with either high dose/low affinity or low dose/high affinity antigen, our data additionally show that T cells with a similar history of primary expansion have a similar capacity to expand during secondary infection, independent of effector lineage. These data are consistent with a recent report showing an inverse correlation between primary T-cell expansion and memory T-cell development (40).…”
Section: Discussionsupporting
confidence: 83%
“…Antigen presentation by BMMo was assessed as described (86,87). BMMo were generated in 10% FBS and 10% CMG14-12 supernatant fluids (60) and infected with L. monocytogenes strain 10403S or pulsed with LLO peptide ± IFNγ priming.…”
Section: S Rrna Illumina Sequencing and Analysismentioning
confidence: 99%
“…At one HPI, infected BMMo were washed with Dulbecco's PBS and Gentamycin was added. Splenic CD4 T cells were isolated from LLO56tg mice (86), bearing a TCR specific for LLO190-225, were isolated using a CD4 negative selection kit (Miltenyi Biotech, Bergisch Gladbach, Germany) and added to the macrophage cultures. After 24 hours, cells were stained for CD4 (eFluor450, Clone RM4-5,…”
Section: S Rrna Illumina Sequencing and Analysismentioning
confidence: 99%
“…Weber and colleagues demonstrated that Listeria-specific T cells expressing distinct Listeria-specific TCRs with equal TCR avidity displayed different immune responses against Listeria infection in two transgenic (Tg) mice, and that it was caused by the difference in TCR avidity of Listeria-specific T cells to unknown self-antigens during thymic education. 44,45 It is well known that the strength of TCR avidity to unknown self-antigens in T cells can be evaluated by the levels of CD5 expression. 41,[46][47][48] In fact, notable difference was observed in CD5 expression between T cells from the two TCR-Tg mice described previously.…”
Section: Discussionmentioning
confidence: 99%